Efektivitas Flavonoid Biskuit Daun Ubi Jalar Ungu (Ipomoea Batatas L.) Terhadap Kadar Hormon Prolaktin Dan Produksi Asi Ibu Menyusui - Desni Irawati; Sri Rahayu; Sri Endang Windiarti (Universitas Pahlawan Tuanku Tambusai, 2026)
Breastfeeding mothers often face challenges with insufficient breast milk supply for their baby's nutritional needs. Purple sweet potato leaves contain galactagogues, which can increase breast milk production. Objective: to determine the effectiveness of flavonoids in purple sweet potato leaf biscuits on prolactin levels and breast milk production in breastfeeding mothers. Methods: this was a true experimental study with a pretest/posttest control group design, consisting of two groups: all breastfeeding mothers in the East Purwokerto Community Health Center (Puskesmas) working area, with a sample size of 20 respondents per group. The intervention group was given biscuits containing 1 gram of purple sweet potato leaf extract and the control group was given education on breastfeeding mothers for 14 days. Body weight was measured using a scale, bowel and urinary frequency using a questionnaire, and prolactin levels using an ELISA kit. Bivariate analysis used Wilcoxon and Man-Whitney. Results: The average infant weight after intervention in the intervention group was 2983.50 g, the control group was 2911.40 g (p=0.010), the average number of bowel movements after intervention in the intervention group was 2.60 times, the control group was 2.25 times (p=0.461), the average number of urinations after intervention in the intervention group was 6.90 times, the control group was 6.20 times (p=0.040), the average prolactin hormone level after intervention in the intervention group was 265.15 ng/ml, the control group was 195.90 ng/ml (p=0.008). Conclusion: Giving purple sweet potato leaf biscuits is effective in increasing prolactin hormone levels and breast milk production in breastfeeding mothers.